Normalized differential conductance to study current conduction mechanisms in MOS structures. (December 2018) - Nouibat, T.H.; Messai, Z.; Chikouch, D.; Ouennoughi, Z.; Rouag, N.; Rommel, M.; Frey, L.
Abstract: In this paper, the conduction mechanisms in MOS structures are investigated using Normalized Differential Conductance (NDC). It is shown that NDC can be applied successfully for the determination of conduction mechanism parameters in MOS devices. The method allows the separation of various components of conduction current and determines the permissible voltage ranges for the determination of the conduction mechanism parameters through the device. The procedure is illustrated by applying it to simulated and experimental current-voltage (I-V) characteristics. The limitations of such parameters extraction are also investigated. A qualitative favorable comparison between experimental data and simulated results is also obtained.